Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing: System Demonstrations 2018
DOI: 10.18653/v1/d18-2025
|View full text |Cite
|
Sign up to set email alerts
|

LIA: A Natural Language Programmable Personal Assistant

Abstract: We present LIA, an intelligent personal assistant that can be programmed using natural language. Our system demonstrates multiple competencies towards learning from humanlike interactions. These include (i) the ability to be taught reusable conditional procedures, (ii) ability to be taught new knowledge about the world (concepts in an ontology) and (iii) the ability to be taught how to ground that knowledge in a set of sensors and effectors. Building such a system highlights design questions regarding the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…However, most agents do not adapt to the phrasing and interest of a specific end user. It has recently been shown that new functionalities can be added to an agent from user instruction (Azaria et al, 2016;Labutov et al, 2018). However, the user instruction only provides one instance of a general instruction template and the agent is challenged to generalize to variations of the instance given during instruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most agents do not adapt to the phrasing and interest of a specific end user. It has recently been shown that new functionalities can be added to an agent from user instruction (Azaria et al, 2016;Labutov et al, 2018). However, the user instruction only provides one instance of a general instruction template and the agent is challenged to generalize to variations of the instance given during instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Current commercial conversational agents such as Siri, Alexa or Google Assistant come with a fixed set of simple functions like setting alarms and making reminders, but are often not able to cater to the specific phrasing of a user or the specific action a * These two authors contributed equally user needs. However, it has recently been shown that it is possible to add new functionalities to an agent through natural language instruction (Azaria et al, 2016;Labutov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava et al (2017) used natural language explanations to teach new concepts. Relatedly, Labutov et al (2018) introduced LIA, a programmable personal assistant that learned from user-provided condition-action rules. Furthermore, Weigelt et al (2020) introduce an approach for teaching systems new programmatic functions from language that explicitly reasons about whether utterances contain "teaching intents," a mechanism that is similar to our procedure for returning NOT-SURE.…”
Section: Related Workmentioning
confidence: 99%
“…Building AI personal assistants is always a fascinating research topic ever since the middle of last century [1]- [3], [11]. Many successful personal assistant products, such as Apple Siri, Google Now, and Amazon Alexa, emerged in the last decades [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many successful personal assistant products, such as Apple Siri, Google Now, and Amazon Alexa, emerged in the last decades [5]. However, almost all existing AI personal assistants act as service terminals, who answer users' questions, control home automation devices, play music, and even manage users' calendars with verbal commands [7]- [9], [11], [13].…”
Section: Introductionmentioning
confidence: 99%